2021
DOI: 10.1177/0023830920986174
|View full text |Cite
|
Sign up to set email alerts
|

Context Matters for Tone and Intonation Processing in Mandarin

Abstract: In tonal languages such as Mandarin, both lexical tone and sentence intonation are primarily signaled by F0. Their F0 encodings are sometimes in conflict and sometimes in congruency. The present study investigated how tone and intonation, with F0 encodings in conflict or in congruency, are processed and how semantic context may affect their processing. To this end, tone and intonation identification experiments were conducted in both semantically neutral and constraining contexts. Results showed that the overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
1
1
0
Order By: Relevance
“…Standard Chinese thus seems to favor preserving tonal identity at the lexical level even at the risk of intonation misidentification. This is also reflected in the high accuracy rate in native listeners' lexical tone identification regardless of intonation type and their difficulty in recognizing statement vs. question, especially when the utterance-final tone is T35 (Yuan 2011, Liu et al 2021. A similar asymmetry in intonation identification (between rising and falling tones) has also been reported in neural processing studies (Ren et al 2009, Ren et al 2013, Liu et al 2016.…”
Section: Intonation For Linguistic Functions: Asking Questionssupporting
confidence: 57%
“…Standard Chinese thus seems to favor preserving tonal identity at the lexical level even at the risk of intonation misidentification. This is also reflected in the high accuracy rate in native listeners' lexical tone identification regardless of intonation type and their difficulty in recognizing statement vs. question, especially when the utterance-final tone is T35 (Yuan 2011, Liu et al 2021. A similar asymmetry in intonation identification (between rising and falling tones) has also been reported in neural processing studies (Ren et al 2009, Ren et al 2013, Liu et al 2016.…”
Section: Intonation For Linguistic Functions: Asking Questionssupporting
confidence: 57%
“…On the contrary, those with Tone-2 final syllables were the most difficult ones to identify. Liu et al (2021) examined the identification of Standard Mandarin intonation with semantically neutral context and semantically constraining context. They found that, in syntactically unmarked polar questions, T4 (HL) had slightly higher identification accuracy in semantically constraining context, but had marginally lower accuracy in nonconstraining context than T2 (LH).…”
Section: Literature On Tune Identificationmentioning
confidence: 99%